2002
DOI: 10.1080/09603120120110077
|View full text |Cite
|
Sign up to set email alerts
|

Spectral ultraviolet albedo of roofing surfaces and human facial exposure

Abstract: Spectral field measurements were used to quantify the ultraviolet (UV) spectral albedos of four different metallic roofing surfaces. The effect of the albedos of two of these surfaces on erythemal exposure to human facial anatomical sites was quantified by UV dosimetry. The albedos of all roofing surfaces were greater than the albedo of grass. Little SZA dependence was observed for any of the surfaces. The albedos of the coloured metallic corrugated surfaces were strongly dependent on wavelength in the UVA, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 9 publications
3
19
0
1
Order By: Relevance
“…There is some photon noise present at the shorter wavelengths, but this does not affect the overall spectral distribution. The spectral RRG UV measured due to vertical surfaces is in agreement with the work of Lester and Parisi [18] in which it was found that galvanised (zinc coated steel) corrugated metal at 305nm had an albedo of 0.27. The measured spectral RRG UV is approximately 0.3 at most wavelengths in Figure 1, slightly higher than the albedo measured by Lester and Parisi.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There is some photon noise present at the shorter wavelengths, but this does not affect the overall spectral distribution. The spectral RRG UV measured due to vertical surfaces is in agreement with the work of Lester and Parisi [18] in which it was found that galvanised (zinc coated steel) corrugated metal at 305nm had an albedo of 0.27. The measured spectral RRG UV is approximately 0.3 at most wavelengths in Figure 1, slightly higher than the albedo measured by Lester and Parisi.…”
Section: Discussionsupporting
confidence: 89%
“…The study for horizontal albedo of roofing material by Lester and Parisi [18] shows high albedo recorded for shiny and coated horizontal surfaces, but does not consider vertical surfaces. However, in many industrial work sites, it can be commonplace to use the metal roof cladding as wall cladding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Albedo also varies according to wavelength 14 which is important to biological processes that are wavelength specific. Albedo of metal surfaces has been investigated 13,15 on a horizontal plane. McKenzie et al 13 found an albedo of 0.18 for shiny corrugated iron, but Lester and Parisi 15 carried out a more extensive investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Albedo of metal surfaces has been investigated 13,15 on a horizontal plane. McKenzie et al 13 found an albedo of 0.18 for shiny corrugated iron, but Lester and Parisi 15 carried out a more extensive investigation. The surfaces in this study consisted of metallic roof sheeting in both galvanised (zinc coated stainless steel) and colour coated stainless steel sheets with albedo measurements ranging from 0.25 to 0.32 depending on wavelength for the galvanised sheeting and 0.03 to 0.12 depending on wavelength and colour for the colour sheeting.…”
Section: Introductionmentioning
confidence: 99%